Symptoms and Signs in Pediatric Surgery - Kaiser, Georges L. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
This concise textbook of pediatric surgery is designed to guide the reader logically from symptoms and signs to diagnosis and treatment. Each chapter is devoted to one of 35 key symptoms and signs, which are organized according to six body regions: head, neck, chest, abdomen, urogenital system, and back. In each case, a brief assessment of the presenting sign/symptom and differential diagnosis is followed by discussion of occurrence, clinical presentation and significance, diagnostic work-up, treatment, and prognosis. Informative tables, illustrations, and up-to-date references are included throughout. Readers will also have access to an e-learning tool developed in collaboration with the Institute of Medical Education, University of Bern, which highlights the characteristics of pediatric surgical disorders and their treatment and includes clinical, radiological, and intraoperative images.   Every physician and surgeon, whether specialist or generalist, who cares for children will find this book to be an invaluable source of information. It is based on the extensive personal experience of the author, which includes teaching at all levels and training of pediatric surgeons.